Characteristics of and Experience Among People Who Use Take-Home Naloxone in Skåne County, Sweden - Troberg, Katja; Isendahl, Pernilla; Blomé, Marianne Alanko; Dahlman, Disa; Håkansson, Anders (Frontiers in Public Health, 2022)
Background Opioid overdose related injury or death can be prevented by bystander naloxone administration. For naloxone to be present when and where overdoses occur, opioid prevention education and naloxone distribution (OPEND) must be established on a broad level. This is the 30-month follow-up of the first multi-site naloxone project in Sweden, implemented at 31 units in the County of Skåne 2018. Aim To address participant characteristics and factors associated with returning for naloxone replenishment and with having used naloxone for overdose reversal. An additional aim was to describe self-reported reasons for naloxone replenishment and overdose experiences. Methods Data were collected through questionnaires at baseline and upon replenishment of the initial and subsequent naloxone kit. Descriptive statistics was used to address participant characteristics, those returning for refill and reporting overdose reversals. Chi-2 test was used for variable comparison between groups. Factors associated with overdose reversals were examined by logistic regression analysis. Reasons for naloxone replenishment, overdose situation and management were presented descriptively. Results Among 1079 study participants, 22% (n=235) returned for refill, of which 60% (n=140) reported a total of 229 overdose reversals. Reversals were more likely to be reported by participants trained at NEPs [adjusted odds ratio (AOR)=5.18, 95% Confidence interval (CI)=3.38-7.95)], with previous experience of own (AOR=1.63, 95% CI=1.03-2.58) or witnessed (AOR=2.12, 95% CI=1.05-4.29) overdose, or who had used sedatives during the last 30 days before initial training (AOR=1.56, 95% CI=1.04-2.33). A majority of overdoses reportedly occurred in private settings (62%), where the victim was a friend (35%) or acquaintance (31%) of the rescuer. Conclusion Participants with own risk factors associated with overdose were more likely to report naloxone use for overdose reversal, which was the main reason for naloxone replenishment. Knowledge on overdose management was high and apart from administering naloxone, a majority used additional strategies recommended by the project. The findings indicate that implementation of multi-site OPEND is feasible and reaches at-risk individuals in settings with limited previous harm reduction strategies and favours a further scaling up of naloxone programs in similar settings.